1982
DOI: 10.1128/iai.35.1.270-275.1982
|View full text |Cite
|
Sign up to set email alerts
|

Serum resistance among Escherichia coli strains causing urinary tract infection in relation to O type and the carriage of hemolysin, colicin, and antibiotic resistance determinants

Abstract: The sensitivity to normal human serum of 91 smooth strains of Escherichia coli isolated from urinary tract infections was determined. Production of hemolysin, which was common and associated primarily with the types 04, 06, 018, and 075, was significantly correlated with high levels of serum resistance, both within the total population and within individual 0 types. In contrast, serum resistance was not significantly associated with antibiotic resistance (whether transmissible or not), with colicinogeny in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 33 publications
3
47
1
1
Order By: Relevance
“…Seven virulence factors (VFs), including type 1 pilus (pil), pilus associated with pyelonephritis (pap), S fimbriae (sfa), afimbrial adhesin I (afaI), hemolysin (hly), aerobactin (aer) and cytotoxic necrotizing factor 1 (cnfI) have been documented to play an important role in causing human UTI (2). Several serotypes such as O1, O2, O4, O6, O8, O16, O18, O22, O25 and O75 are preferentially associated with UPEC strains and each of the uropathogenic virulence factors is significantly associated with these serotypes (1,6,8). E. coli strains isolated from dogs and cats with UTI have high prevalence of hly and clustered in 5 serotypes including O2, O4, O6, O7 and O18 (7).…”
mentioning
confidence: 99%
“…Seven virulence factors (VFs), including type 1 pilus (pil), pilus associated with pyelonephritis (pap), S fimbriae (sfa), afimbrial adhesin I (afaI), hemolysin (hly), aerobactin (aer) and cytotoxic necrotizing factor 1 (cnfI) have been documented to play an important role in causing human UTI (2). Several serotypes such as O1, O2, O4, O6, O8, O16, O18, O22, O25 and O75 are preferentially associated with UPEC strains and each of the uropathogenic virulence factors is significantly associated with these serotypes (1,6,8). E. coli strains isolated from dogs and cats with UTI have high prevalence of hly and clustered in 5 serotypes including O2, O4, O6, O7 and O18 (7).…”
mentioning
confidence: 99%
“…Complement resistance confers the possibility to spread to different body sites through the bloodstream. Hallström et al [54] reported the relationship of bacterial resistance to NHS with sepsis severity, and other authors have associated it to different kinds of extraintestinal infections [5557].…”
Section: Discussionmentioning
confidence: 99%
“…20 For each experiment, a control was performed using inactivated fresh plasma (IFP), with incubation at 55 C for 30 minutes to disrupt the classical and alternative pathways of the complement cascades. 19 Overnight cultures were adjusted to 10 6 CFUs/mL in LB for a final volume of 2 mL. FFP alone (Condition A-100 μL of bacterial culture +100 μL of FFP; Condition B-100 μL bacterial culture + 100 μL of IFP) and FFP + PLT protection solution (SPP+; Condition C-100 μL of bacterial culture + 33 μL of FFP + 67 μL of SPP+; Condition D-100 μL of bacterial culture + 33 μL of IFP + 67 μL of SPP+) were tested.…”
Section: Serum Survival Assaymentioning
confidence: 99%
“…Regarding the discrepancy in terms of LT in this environment, we tested three different hypotheses: 20 The control strains, CFT073 and K-12 MG1655, killed 10 of 10 (super killer) and zero of 10 mice in 24 hours (nonkiller), respectively. §S/R = sensitivity or resistance as defined by Hughes et al 19 kSPP+ is a PLT protection solution. Once the serum was heat-inactivated, all of the strains (TTBI and IAI) became resistant to the serum with and without SPP+ (data not shown).…”
Section: Apc-like Medium Growth At 24 Cmentioning
confidence: 99%